Большой русско-французский словарь: 200 000 слов и словосочетаний - Щерба Л. В. Лев Владимирович; Матусевич М. И. Маргарита Ивановна; Никитина С. А. Софья Александровна; Воронцова Т. П.; Желле Т.; Семина И. А.; Еременко Т. Ю. (А - Я)
Авторы указаны на обороте титульного листа.